Anthelmintic efficacy of the aqueous crude extract of Euphorbia hirta Linn in Nigerian dogs (2005)
The anthelmintic efficacy of the aqueous crude extract of Euphorbia Itirta Linn was studied in 20 Nigerian dogs that were naturally infected with nematodes. They were randomly divided into 4 groups. A, B. C and D. Groups A and B each comprised 4 dogs while groups C and D comprised 6 dogs each. Group A animals were untreated, while those in group B were treated with proprietary anthelmintic (Mebendazole). Groups C and D animals were treated with aqueous crude extracts of E. hirta using intramuscular and oral routes, respectively. Two weeks after treatment, blood and faecal samples were collected to evaluate haematological values and faecal egg counts, respectively. The procedure was repeated two weeks later. Results of this study show that the aqueous crude extracts of E. hirta after its administration into local dogs produced a significant increase (P< 0.05) in PCV, RBC. l ib cone.. TWBC and lymphocyte counts. The faecal egg counts also showed a remarkable and significant reduction in the levels of the identified helminths. The reduction in faecal egg counts was more pronounced with the extract administered through the oral route when compared with the intramuscular route. The effects of the plant extracts were broad spectrum in action. The phenol compound present in the plant extract could have caused reduction in worm load through this same mechanism that culminates in exhaustion and death ofworms. Since the aqueous crude extract of £. hirta significantly reduced the faecal egg count of the helminths, it could serve as an anthelmintic agent